Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.bbrep.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ effects on glucose transport and fatty acid oxidation in L6 skeletal muscle cell cultures

Abstract: We examined the effect of Ca2+ on skeletal muscle glucose transport and fatty acid oxidation using L6 cell cultures. Ca2+ stimulation of glucose transport is controversial. We found that caffeine (a Ca2+ secretagogue) stimulation of glucose transport was only evident in a two-part incubation protocol (“post-incubation”). Caffeine was present in the first incubation, the media removed, and labeled glucose added for the second. Caffeine elicited a rise in Ca2+ in the first incubation that was dissipated by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 66 publications
0
9
0
3
Order By: Relevance
“…Next, we assessed whether increased mitochondrial respiration in astrocytes exposed to rTat and cocaine is mediated by an increase in the rate of [Ca 2+ ] m uptake. It has been shown that cocaine/ionomycin treatment stimulates mitochondrial metabolism in a Ca 2+ -dependent manner 36 . Since we hypothesized MCU-mediated Ca 2+ uptake as a nodal point for the astrocyte metabolic switching during rTat/cocaine stimulation, we assessed if blocking MCU-mediated [Ca 2+ ] m uptake in astrocytes could prevent the decreased lactate and increased Acetyl-CoA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we assessed whether increased mitochondrial respiration in astrocytes exposed to rTat and cocaine is mediated by an increase in the rate of [Ca 2+ ] m uptake. It has been shown that cocaine/ionomycin treatment stimulates mitochondrial metabolism in a Ca 2+ -dependent manner 36 . Since we hypothesized MCU-mediated Ca 2+ uptake as a nodal point for the astrocyte metabolic switching during rTat/cocaine stimulation, we assessed if blocking MCU-mediated [Ca 2+ ] m uptake in astrocytes could prevent the decreased lactate and increased Acetyl-CoA.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we showed FAO to play a significant role in sustaining inflammatory responses in the CNS and therapeutic interventions targeting FAO could well be appreciated. Cocaine exposure is expected to increase intracellular Ca 2+ transients through G-protein coupled receptors (GPCR) stimulation 36 . Likewise, Tat is known to cause over activation of NMDA receptors and intracellular Ca 2+ -dependent damage to oligodendrocytes and myelin 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cytosolic calcium would stimulate glycogen phosphorylase which in turn activate glycogenolysis and tricarboxylic acid cycle (Balu, Ouyang, Parakhia, Pitake, & Ochs, 2016). Conventional protein kinase C (cPKC) and Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) are potential targets of Ca 2+ , leading to increase in glucose uptake (Huang & Czech, 2007).…”
Section: Fer Rsv and Egcg Regulate Glucose Utilization Via Parallmentioning
confidence: 99%
“…] i в адипоцитах и других клетках-мишенях инсулина может повышать резистентность к инсулину путем фосфорилирования транспортера глюкозы 4 типа и других субстратов, чувствительных к инсулину, что снижает эффективность инсулинопосредованного поглощения глюкозы [18].…”
Section: +unclassified